BIOLOGICAL EVALUATION, QSAR AND MOLECULAR MODELING STUDIES OF 2,4-DICHLOROBENZOIC ACID DERIVATIVES AS ANTIMICROBIAL AGENTS - SAMRIDHI THAKRAL; VIKRAMJEET SINGH (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The aim of this study was to evaluate 2,4-dichlorobenzoic acid derivatives as antimicrobial agents through in vitro, QSAR and molecular docking studies. Methods: The compounds were subjected to in vitro antimicrobial screening by test tube dilution method and the structural characteristics governing the antimicrobial potential were studied using QSAR methodology. These compounds were also screened for docking simulation to find out binding confirmation of reported compounds with PDB 1aj0 and 5fsa using AutoDock tools and discovery studio. Results: The antimicrobial evaluation data indicated that compounds 13 and 18 were found to be the most effective against all the bacterial strains and Aspergillus niger while compounds 1 and 14 exhibited more antifungal potential against Candida albicans. QSAR studies confirmed the role of molar refractivity and Balaban index (J) as controlling parameters for antimicrobial potential. Molecular modeling study revealed that compounds interact with the active site of PDB by hydrophobic, hydrogen bonding, and Van der Wall interactions. Conclusion: These test compounds were identified as potent candidates for the control of microbial strains tested, and structural relationship with activity may provide valuable information for further design and synthesis of compounds with antimicrobial potential.